Manajemen Survival Pengelolaan Program Tahfidzul Quran (Studi Komparasi di MA Tarbiyatut Tholabah Dan MA Al-Fathimiyah) - Azizah, Khoridatul; Wildan Thobibi Bahja, Ahmad; Maghfiroh, Marjiatul; Qomaruddin, Moch; Solikhah, Mar'atus (AL MURABBI, 2024)
This study aims to: 1) outline the Tahfidzul Quran programs at MA Tarbiyatut Tholabah and MA Al-Fathmiyah Lamongan, 2) examine how each school manages the survival of their Tahfidzul Quran programs, and 3) compare the differences in management approaches between the two schools. It employs a qualitative methodology with a multi-site study design, utilizing observation, interviews, and documentation for data collection. Analysis follows Huberman's method, involving data collection, reduction, presentation, and conclusion drawing. Findings indicate that while MA Tarbiyatut Tholabah's Takhassus Tahfidz program is internally managed, MA Al-Fathimiyah's program is overseen by LPTQ and implemented within a formal institution. Additionally, MA Tarbiyatut Tholabah's program is integrated with the boarding school, while MA Al-Fathimiyah's is executed by the formal institution on behalf of LPTQ, which is owned by the Foundation.